Factors Associated with Sibling Rivalry Behavior in Toddlers - Rabia Zakaria; Yusni Podungge; Rahma Dewi Agustini (JOURNAL OF NONCOMMUNICABLE DISEASES, 2021)
Sibling rivalry is a form of relationship conflict with siblings that can affect individual development, both positively and negatively and give impact on the child, parents, and society. Puskesmas Kabila is one of the health centers in Bone Bolango Regency, Gorontalo, which has the lowest achievement of health services for children under five, namely 61.1% in 2019 and as many as 70% of mothers who have more than one toddler tend to experience sibling rivalry. This literature study aims to determine the factors associated with the behavior of sibling rivalry in toddlers. This literature study research was conducted by examining 13 literatures consisting of 8 journals and 5 books. The results will be analyzed descriptively. The independent variable in this study is the factors examined in research journal articles, while the dependent variable is the behavior of sibling rivalry in children under five. The research instrument used was a data table to make it easier to interpret the results of a literature study. The results of the literature study show that the factors associated with sibling rivalry include: parenting styles, emotional intelligence, parental knowledge, differences in gender and age as well as parents' attitudes towards children.